Methods to solve half-plane partial slip contact problems. (15th December 2018) - Hills, D.A.; Ramesh, R.; Barber, J.R.; Moore, M.R.
Abstract: There exists a family of methods for finding the extent of partial slip in contact problems between elastically similar bodies, capable of idealisation by half-planes. Closed form solutions are given to problems subject to a constant normal load and subsequent application of either an increasing shear force or differential bulk tension parallel with the surface. The starting point may be either a sliding contact (as is customary), or a fully adhered contact. The corrections required to impose a point-wise interpretation of Coulomb's law of friction may be either in the form of a shear traction distribution or as dislocation arrays. The latter, when applied to the fully adhered contact, has the merit of automatically preserving the locked-in relative surface strains.